Digital Inkjet Printing of High‐Efficiency Large‐Area Nonfullerene Organic Solar Cells. Issue 7 (1st April 2019) - Corzo, Daniel; Almasabi, Khulud; Bihar, Eloise; Macphee, Sky; Rosas‐Villalva, Diego; Gasparini, Nicola; Inal, Sahika; Baran, Derya
Abstract: Novel emerging materials for organic solar cells, such as nonfullerene acceptors, are paving the way for commercialization of organic photovoltaics. Their utilization in unconventional applications, such as conformable and disposable electronics, has turned the focus to inkjet printing as a fabrication method with advantages including low material usage, rapid digital design changes, and high resolution. In this work, the fabrication of efficient nonfullerene acceptor devices through inkjet printing for organic photovoltaic applications is reported for the first time. The engineering of printable poly‐3‐hexylthiophene:rhodanine‐benzothiadiazole‐coupled indacenodithiophene (P3HT:O‐IDTBR) inks is centered on tuning the rheological properties for proper droplet ejection and the selection of solvents, including hydrocarbons, that meet solubility and volatility requirements to avoid common inkjet printing complications like nozzle clogging. The optimization of printing parameters including drop spacing and deposition temperatures results in homogeneous P3HT:O‐IDTBR films with device efficiencies of up to 6.47% for small lab‐scale devices (0.1 cm 2 ), comparable with that of spin‐coating or blade‐coating. A 2 cm 2 inkjet‐printed device is also shown to achieve a remarkable efficiency of 6%. To demonstrate their potential usage in customized applications, large‐area devices are fabricated in the shape of a marine turtle with 4.76% efficiency, showcasing the versatility of the inkjet‐printing process for efficient organic photovoltaics. Abstract : 6% large‐area poly‐3‐hexylthiophene:rhodanine‐benzothiadiazole‐coupled indacenodithiophene solar cells are fabricated through inkjet‐printing, matching the performance of coated devices. The optimization and control over the printing process enables the deposition of custom‐shaped 2.2 cm 2 area devices with 4.7% power conversion efficiency. The competitive efficiencies obtained through the engineering of inks with hydrocarbon solvents show the potential for a more environmentally friendly industrial scale‐up.